Challenges of research recruitment in a university setting in England. (20th May 2017) - Vadeboncoeur, Claudia; Foster, Charlie; Townsend, Nick
Summary: The recruitment is an integral part of most research projects in medical sciences involving human participants. In health promotion research, there is increasing work on the impact of environments. Settings represent environments such as schools where social, physical and psychological development unfolds. In this study, we investigated weight gain in students within a university setting. Barriers to access and recruitment of university students within a specific setting, in the context of health research are discussed. An online survey on health behaviours of first year students across 101 universities in England was developed. Ethics committees of each institutions were contacted to obtain permission to recruit and access their students. Recruitment adverts were standardized and distributed within restrictions imposed by universities. Three time points and incentives were used. Several challenges in recruiting from a university setting were found. These included (i) ethics approval, (ii) recruitment approval, (iii) navigating restrictions on advertisement and (iv) logistics of varying university academic calendars. We also faced challenges of online surveys including low recruitment, retention and low eligibility of respondents. From the 101 universities, 28 allowed dissemination of adverts. We obtained 1026 responses at T1, 599 at T2 and 497 at T3. The complete-case sample represented 13% of those originally recruited at T1. Conducting research on students within the university setting is a time consuming and challenging task. To improve research-based health promotion, universities could work together to increase consistency as to their policies on student recruitment.